2017
DOI: 10.1007/s11606-017-4167-y
|View full text |Cite
|
Sign up to set email alerts
|

Overtreatment and Deintensification of Diabetic Therapy among Medicare Beneficiaries

Abstract: Medicare recipients are more frequently overtreated than undertreated for diabetes. Medicare recipients who are overtreated for diabetes rarely have their regimens deintensified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 34 publications
5
53
2
1
Order By: Relevance
“…This is one of the first national studies to evaluate potential overtreatment and deintensification of diabetes management in a subgroup of nursing home residents with LLE/AD. Although patterns of overtreatment and deintensification in diabetes were described previously in the literature, 14,16,17,41,42,[49][50][51] only one investigation examined the influence of life expectancy on diabetes management. 15 The proportion of residents who were overtreated in our sample (nearly half) aligns with previously reported estimates from large observational studies conducted in non-nursing home populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is one of the first national studies to evaluate potential overtreatment and deintensification of diabetes management in a subgroup of nursing home residents with LLE/AD. Although patterns of overtreatment and deintensification in diabetes were described previously in the literature, 14,16,17,41,42,[49][50][51] only one investigation examined the influence of life expectancy on diabetes management. 15 The proportion of residents who were overtreated in our sample (nearly half) aligns with previously reported estimates from large observational studies conducted in non-nursing home populations.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies of community-dwelling older adults with diabetes identified several other factors associated with increased likelihood for deintensification including more chronic conditions, greater frailty, and more outpatient visits. 41,42 One could argue that patients with these characteristics are common among older adults in the nursing home setting and that some may actually serve as drivers of institutionalization. Taken together, our findings indicate that in older CLC residents with LLE/AD, a population in which complex comorbidity and frailty are likely common, deintensification is not so much driven by individual clinical characteristics, but rather by a general concern for hypoglycemic adverse events that apply to all older adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucose‐lowering medications to treat diabetes have been blamed for up to 25% of emergency hospitalizations in the USA to treat hypoglycemia . Diabetic treatments have also been implicated in cardiovascular events, cognitive impairment, fractures, and death . Aggressive hypertension treatments often cause hypotension with potentially severe side effects, including acute renal failure, hyponatremia, hypokalemia, and syncope .…”
Section: Overtreatment Is a Public Health Problemmentioning
confidence: 99%
“…Recent guidelines for treating diabetes and hypercholesterolemia already encourage setting individualized goals, but the challenge now, according to Huang, is to encourage physicians to adopt these guidelines. The American Geriatrics Society and the American Diabetes Association stress the increased risks of hypoglycemia and reduced benefits of aggressive treatment in older patients with mild forms of the disease and endorse higher glycemic targets . Likewise, the US Preventive Services Task Force's recent guidance on statin therapy recommended that adults aged 40–75 years without a history of CVD and 10‐year risk of a cardiovascular event of 10% or greater should use a low‐ to moderate‐dose statin to prevent CVD events.…”
Section: Addressing the Problemmentioning
confidence: 99%